Efficacy and Safety of Vitamin D Supplementation for Pulmonary Tuberculosis: A Systematic Review and Meta-analysis - Ji WANG; Malong FENG; Shidong YING; Jianfang ZHOU; Xiaoqing LI (Tehran University of Medical Sciences, 2018)
Background: Vitamin D might be promising to serve as an adjunctive therapy for pulmonary tuberculosis (TB). However, the results remained controversial. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of vitamin D in patients with pulmonary TB. Methods: Medline, SCOPUS, Google Scholar, EMBASE, Springer, and Science Direct were searched electronically from inception to Oct 2016. Randomized controlled trials (RCTs) and controlled clinical trials (CCTs) assessing the effect of vitamin D plus anti-tuberculosis treatment (ATT) versus placebo plus ATT on the treatment of pulmonary TB were included. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. Data were analyzed using RevMan 5.3 software. Results: Five studies were included in this meta-analysis. Overall, compared with placebo intervention, vitamin D supplementation was found to have no significant effect on sputum smear negative conversion rates (RR=0.99; 95% CI=0.91 to 1.07; P=0.77), BMI (MD=0.11; 95% CI=-0.85 to 1.07; P=0.82) and ESR (MD=-2.29; 95% CI=-8.87 to 4.30; P=0.50). Conclusion: Vitamin D supplementation showed no influence on the improvement of sputum smear-negative conversion rates and BMI, as well as the decrease in ESR.